2020
DOI: 10.1038/s41467-019-13921-9
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-wide Mendelian randomization study to uncover tissue-dependent regulatory mechanisms across the human phenome

Abstract: Developing insight into tissue-specific transcriptional mechanisms can help improve our understanding of how genetic variants exert their effects on complex traits and disease. In this study, we apply the principles of Mendelian randomization to systematically evaluate transcriptome-wide associations between gene expression (across 48 different tissue types) and 395 complex traits. Our findings indicate that variants which influence gene expression levels in multiple tissues are more likely to influence multip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 83 publications
0
52
0
Order By: Relevance
“…To address this, recent studies have demonstrated the value of omics studies in predicting the potential effects of a drug target on complex diseases. 37 , 38 Thus, comprehensive assessment of the causal effects of COVID-19 drug targets on disease phenotypes will provide key information regarding their safety issue ( Figure 3 ). 39 …”
Section: Genetic Insights Into Covid-19mentioning
confidence: 99%
“…To address this, recent studies have demonstrated the value of omics studies in predicting the potential effects of a drug target on complex diseases. 37 , 38 Thus, comprehensive assessment of the causal effects of COVID-19 drug targets on disease phenotypes will provide key information regarding their safety issue ( Figure 3 ). 39 …”
Section: Genetic Insights Into Covid-19mentioning
confidence: 99%
“…Two-sample MR analysis 4,5 is particularly popular as these methods can be applied even if the genome-wide association study for the different traits are conducted on nonoverlapping samples. In recent years, the growing sample size of GWAS and volume of publicly available summary-level datasets have facilitated the popularization of MR. MR analyses have led to improved understanding of epidemiological associations, discovery of new drug targets 3,6 , and new insights into biological mechanisms through applications to large-scale omics data [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another MR study has shown that acetylcholinesterase expression may be causally associated with raised blood pressure ( Richardson et al , 2020 ). ACHE encodes the target for acetylcholinesterase inhibitors such as donepezil and galantamine, which are licenced treatments for Alzheimer’s disease ( Lane et al , 2018 ).…”
Section: Mr In Drug Development—nature’s Randomized Controlled Trialmentioning
confidence: 99%
“…Tissue diversity has been more thoroughly explored for eQTL data ( Gamazon et al , 2018 ; Taylor et al , 2019 ; Richardson et al , 2020 ). For example, an MR study found that FBN2 expression in heart tissue was linked to diastolic blood pressure, whereas FBN2 expression in lung tissue was linked to forced vital capacity ( Richardson et al , 2020 ). Such evidence suggests that biologically relevant tissues may be crucial for molecular-level MR projects.…”
Section: Future Directions and Outstanding Questionsmentioning
confidence: 99%